Seasonal changes of root hydraulic conductance (K RL) in four forest trees: an ecological interpretation - Nardini, A; Gullo, M A Lo; Salleo, S (Plant Ecology, 1998)
This paper deals with the possibility of relating root hydraulic parameters to an ecological index describing the continentality/oceanicity of four forest trees. Root hydraulic conductance (KR) of seedlings of Fagus sylvatica L., Quercus ilex L., Quercus suber L. and Quercus pubescens Willd. was measured in May, August and November 1996. KR was calculated in terms of the relation of the water ﬂow through intact root systems in situ measured with the pressure chamber, and the pressure driving the ﬂow. The sufﬁciency of the root system to supply the foliage was estimated by dividing KR by the seedlings leaf surface area (AL) thus obtaining KRL. In the spring, KRL was largest in F. sylvatica and smallest in Q. pubescens with intermediate values recorded in Q. ilex and Q. suber. All the species studied showed a large decline in KRL just prior to the winter rest except for Q. suber which mantained KRL approximately constant through the period of study. In most cases, KRL changed in accordance with analogous changes in the ﬂow. When the total seedlings’ leaf surface area (AL) was plotted versus KRL, it appeared that KRL of Q. pubescens increased with AL, proportionally, while KRL of F. sylvatica was inversely related to AL. This, together with the largest KRL recorded in the summer in Q. pubescens, was interpreted as advantageous to this species (which is adapted to semi-arid environments) in that: (a) roots could supply water to foliage efﬁciently even during the adverse season and (b) the foliage growth could be sustained even in summer. No statistically signiﬁcant relation of KRL to the continentality index calculated for the four species studied on the basis of their European distribution, was found to exist. Nonetheless, our data appear to be encouraging for future research aimed at better interpreting the typical distribution areas of plant species.
Keywords: continentality index; Fagus sylvatica; Quercus ilex; Quercus pubescens; Quercus suber; root hydraulic efficiency